Study of environmental quality along walking and cycling pathways - Chang, Yong Sheng (2017)
Many factors come into play when choosing a route to travel to one’s destination. There is no one determining factor, as the priorities and perceptions of the user may differ vastly from others. Walking is an essential mode of transportation used by almost everyone on a daily basis. With the increasing popularity of personal mobility devices (PMDs), as well as the implementation of a “Walk Cycle Ride SG” lifestyle by the government, land-scarce Singapore finds itself struggling to offer dedicated spaces to both pedestrians and cyclists. This results in the common problem of cyclists travelling on pedestrian walkways, causing discomfort and posing potential threats of accidents. As such, there is a need to identify how pedestrians and cyclists effectively choose their routes, when given different route choices leading from the origin to the same destination. Knowledge of route choice will assist future infrastructural planning to construct routes catering to each group of users, so as to minimise the problem of co-sharing a pathway. This project assesses how various infrastructural compatibility factors affect the selection of routes leading from the origin to the same destination. However, due to the nature of the sample area, PMD users will not be assessed in this study. A preliminary free association survey was conducted to identify existing factors that differ across available routes. From the survey, distance was shown to be the most prominent factor for pedestrians, amongst several others. Data in the form of distance and pollution indices were collected and compared to highlight the extent of differences among the routes.